2021
DOI: 10.1093/heapro/daab036
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mental burnout among Israeli Home Front Command soldiers during the COVID-19 pandemic

Abstract: Abbreviations GRRs, generalized resistance resources; HFC, Home Front Command; IDF, Israeli Defense Forces; SOC, sense of coherence; SOT, sense of threat; SRH, self-rated health; SRRs, specific resistance resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…In addition, high levels of meaningfulness were associated with high levels of personal accomplishment. These results replicate the findings in the existing literature [32,33] regarding the relationship between SOC and mental health. Stoyanova and colleagues [16], for example, reported strong associations between the three components of SOC and the burnout dimensions among health care workers and suggested that the combination of the cognitive, motivational, and instrumental aspects of SOC can predict burnout.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, high levels of meaningfulness were associated with high levels of personal accomplishment. These results replicate the findings in the existing literature [32,33] regarding the relationship between SOC and mental health. Stoyanova and colleagues [16], for example, reported strong associations between the three components of SOC and the burnout dimensions among health care workers and suggested that the combination of the cognitive, motivational, and instrumental aspects of SOC can predict burnout.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported in an Israeli study among military reserve rescue teams of the Home Front Command. They were recruited and assigned to reinforce Israel's national emergency medical service at its operational call center (Avishai Antonovsky et al, 2021).…”
Section: Mental Hazards In the Work Of First Respondersmentioning
confidence: 99%
“…Mental fitness is more specific and task oriented than SOC, but the stronger the people's SOC, the easier it will be for them to develop and maintain a high level of mental fitness. For example, in the study described earlier of military rescue soldiers in Israel's national emergency medical service during the COVID-19 pandemic, SOC was the best predictor of (and inversely related to) sense of threat, state anxiety, and burnout (Avishai Antonovsky et al, 2021). In that study, it was also found that a subgroup of soldiers who had been given structured mental preparation based on salutogenic principles of providing information, strengthening resistance resources, and emphasizing meaningfulness exhibited less burnout and a higher degree of subjective well-being than those who had not received such preparation (Danon et al, 2020).…”
Section: Mental Hazards In the Work Of First Respondersmentioning
confidence: 99%
“…One that has already been completed was conducted during the COVID-19 pandemic in April 2020. We examined SOC as a predictor of well-being, burnout, state anxiety, and sense of threat among Israeli Home Front Command reserve soldiers who were assigned to assist in a medical emergency call center (Avishai Antonovsky et al, 2021;Danon et al, 2020). SOC was found as a strong predictor of the aforementioned variables (and stronger than self-efficacy).…”
Section: The Growing Awareness Of Soc In the Idfmentioning
confidence: 99%